THE ROLE OF ACCOUNTING INFORMATION SYSTEMS FOR INCREASING THE SCALE OF MSMEs IN SUSTAINABLE DEVELOPMENT - Camelya Adelyani Br Hutagalung; Indra Fauzi; Ardhansyah Putra Hrp; Yudi Harianto; Melissa Rambe (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to analyze the role of accounting information systems (AIS) in increasing the scale of micro, small and medium enterprises (MSMEs) in the context of sustainable development. By utilizing AIS, MSMEs are expected to be able to improve operational efficiency, accuracy of financial data, and quality of decision-making. This research will review related literature, conduct case studies on several MSMEs, and analyze qualitative and quantitative data. The results of this study are expected to contribute to the development of an effective AIS model for MSMEs and provide recommendations for MSME actors and other stakeholders in an effort to increase business scale in a sustainable manner.